Metallic FePSe3 nanoparticles anchored on N-doped carbon framework for All-pH hydrogen evolution reaction. (March 2019) - Yu, Jing; Li, Wei-Jian; Zhang, Hongsen; Zhou, Fei; Li, Rumin; Xu, Cheng-Yan; Zhou, Limin; Zhong, Hang; Wang, Jun
Abstract: The present nonprecious hydrogen evolution electrocatalysts deliver high activity either in acid or alkaline media, indicating the urgent demand for development of pH-universal catalysts. In this work, we report a high-performance electrcatalyst based on ternary iron phosphoselenide (FePSe3 ) nanoparticles anchored on N-doped carbon framework for hydrogen evolution reaction (HER) in acidic, neutral and basic media. The FePSe3 nanoparticles with metallic nature enable to fully utilize accessible edge sites, and the highly open yet interconnected three-dimensional framework creates large surface area, exposing abundant active sites and providing convenient charge/ionic diffusion pathway. DFT calculations reveal the synergistic electronic interaction between Se and P, leading to optimal electronic structures and hydrogen adsorption free energy on Fe, P and Se sites, thus facilitating HER kinetics. As a result, the obtained FePSe3 /NC exhibits superior HER activities with low overpotentials of 70, 140.1 and 118.5 mV to afford 10 mA cm −2 current density in acidic, neutral and basic media, as well as robust stability in all-pH range. This work highlights the dual-anion effect to radically construct all-pH HER electrocatalysts. Graphical abstract: fx1 Highlights: FePSe3 nanoparticles were anchored into N-doped carbon framework. The unique structure and optimal hydrogen adsorption energy endow FePSe3 /NC with good HER ability. FePSe3 /NC exhibits superior HER performance in all-pH range from 0 to 14.